Arabidopsis Histone Methyltransferase SUVH5 Is a Positive Regulator of Light-Mediated Seed Germination - Gu, Dachuan; Ji, Rujun; He, Chunmei; Peng, Tao; Zhang, Mingyong; Duan, Jun; Xiong, Changyun; Liu, Xuncheng (Frontiers in Plant Science, 2019)
Plant lifecycle starts from seed germination, which is regulated by various environmental cues and endogenous hormones. Light promotes seed germination mainly by phytochrome B (PHYB) during the initial phase of imbibition, which involves genome-wide light-responsive transcription changes. Recent studies indicated an involvement of multiple epigenetic factors in the control of seed germination. However, few studies have been reported about the role of a histone methyltransferase in light-mediated seed germination process. Here, we identified SUVH5, a histone H3 lysine 9 methyltransferase, as a positive regulator in light-mediated seed germination in Arabidopsis. Loss of function of SUVH5 leads to decreased PHYB-dependent seed germination. RNA-sequencing analysis displayed that SUVH5 regulates 24.6% of light-responsive transcriptome in imbibed seeds, which mainly related to hormonal signaling pathways and developmental processes. Furthermore, SUVH5 represses the transcription of ABA biosynthesis and signal transduction-related genes, as well as a family of DELAY OF GERMINATION (DOG) genes via dimethylation of histone H3 at lysine 9 (H3K9me2) in imbibed seeds. Taken together, our findings revealed that SUVH5 is a novel positive regulator of light-mediated seed germination in Arabidopsis.